Security of tenure vs management prerogative to discharge surplus labour - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (Center for Promoting Ideas (CPI), 2012)
An employee's right to job security has to be balanced with the just requirement of the employer who should be given the opportunity, under certain circumstances, to retrench workers from employment arising from genuine business reasons such as decrease in business activities, perceived advantages of greater mechanisation and technological change, deployment of capital resources in different ways, reorganisation of business operations with a view to enhancing profitability, and reducing losses either generally or in selected areas, among others. In the above circumstances, the law cannot give an answer which can satisfy both parties. Both would have to come to terms with facing harsh realities during time of uncertainty or change. If the employer carries on business and sustains losses, this may lead to insolvency, bankruptcy or winding up. The other option is to sacrifice some workers, thereby preserving the viability of business and the employment of the remaining workers. Therefore, it would not be inaccurate to state that retrenchment is a difficult area of labour law because a balance has to be struck between the two competing interests, the employee’s interest of retaining his security of tenure against the protection of the employer’s business interest and the overriding interest would be preserving the viability of the employer’s business and the employment of the remaining workers. Having said the above, this article will discuss workers security of tenure in employment as opposed to the employer’s prerogative of retrenching workers under certain circumstances.